In perennial allergic rhinitis, RQLQ is improved similarly by Azelastine 0.15 and mometasone furoate - Jean Bousquet, MD; Ludger Klimek, MD; Hans-Christian Kuhl, PhD; Duc Tung Nguyen, MD; Rajesh Kumar Ramalingam, MD; G. Walter Canonica, MD; William E. Berger, MD (World Allergy Organization Journal)
Some double-blind, placebo-controlled trials have shown that Azelastine (Aze) high dose (0.15%) was effective in seasonal (SAR) and perennial allergic rhinitis (PAR). However, there was no long-term comparison between Aze 0.15% and intranasal corticosteroids (INCS) on safety and quality of life in perennial allergic rhinitis.An open-label, active-controlled, parallel-group one-year study comparing mometasone furoate and Aze 0.15% in adults assessed safety over 1 year. Efficacy using the 28-item rhino-conjunctivitis quality of life questionnaire (RQLQ) was a secondary end point.A total of 703 patients were randomized and 687 (97.7%) were included in the intent-to-treat (ITT) population. The present formulation was shown to be safe with long-term use over 12 months, with a mean duration of exposure of 270.7 days.Over the one-year period, there was no significant difference for any RQLQ domains between Aze and mometasone furoate (MF) for all evaluations (baseline, 6, 9, and 12 months). This study suggests that Aze 0.15% and MF display a similar improvement of RQLQ ( 2.80 [2.78] for Aze 0.15% vs 2.81 [2.75] for MF). Clinical trial registry number: NCT00720382.